Ad-hoc, Mobile and Wireless Networks - Coudert, David (Springer, 2017)
This book constitutes the refereed proceedings of the 7th International Conference on Ad-Hoc, Mobile, and Wireless Networks, ADHOC-NOW 2008, held in Sophia-Antipolis, France, September 2008.